Impact of Peer Mentoring Role on Mentors’ Personal Development and Leadership Practices: A study among Undergraduate Emirati Female Students at a Higher Education Institution in the United Arab Emirates - BAROUDI, SANDRA (2019)
Many leadership programs were initiated to increase female’s leadership and reduce gender barriers in most developed and developing countries. Among these programs, a great emphasis was put on the mentoring role due to the benefits it holds on developing females’ self-confidence and leadership skills. Therefore, the purpose of this study was to explore the impact of peer mentoring role on mentors’ personal development and examine the most exemplary leadership practices that the mentoring role nurture in Emirati female undergraduate student mentors in one university at the United Arab Emirates. This study adopted a mixed methods research design in two sequential phases: a qualitative phase to explore mentors’ perceptions followed by a quantitative phase to examine the exemplary leadership skills that the mentoring role has nurtured in them. One-on-one interviews with twenty-two mentors provided the study with an in-depth understanding of the peer mentoring role and its impact on mentors’ academic, personal development, and career related skills. Four main categories were generated from mentors’ responses. This study revealed the vital characteristics for effective mentors as described by the framework of Jacobi and Terrion and Leonard and uncovered new themes that are specific to the context and culture of the participants. For instance, “doing good to others” or, as it is known in Islamic culture, عمل الخير, was the most prominent theme in female mentor participants’ responses regarding their reasons for joining the program. Quantitative data was collected from 94 mentors and 142 mentees through the Student Leadership Practices Inventory Survey (SLPI) self and observer versions. Results from the quantitative analysis demonstrated significant correlations among all SLPI subscales. Quantitative results provided evidence for the association of the peer mentoring role with the development of one’s leadership skills and practices. Among the five leadership practices, Inspire a Shared Vision was not correlated with the impact that the mentoring role has on the development of these exemplary leadership practices. This study implies for curriculum developers in undergraduate programs to create curricula containing an array of peer teaching/mentoring experiences. Faculty role should be integrated and defined when designing the structure and roles of the peer mentoring program. Further research is recommended to explore the impact of peer mentoring programs with wider sample and with students from different backgrounds.